2012
DOI: 10.1097/adt.0b013e3182213f0a
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Personality Dimensions in Egyptian Substance Dependence Patients

Abstract: Objectives:This study was designed to assess the quality of life in a group of Egyptian substance dependence patients by comparing it with World Health Organization (WHO) standards and to assess the correlation between their quality of life and personality dimensions. Methods:A total of 54 patients with substance dependence (after detoxification) were diagnosed by the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders IV over a period of 6 months at the Okasha Institute of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Given such background, traditional healing practices and illegal use of prescriptive medicines are rife and remain as the only recourse for people with substance use disorders in Arab countries [6, 85, 86]. Thus, people with substance use disorders in the Arabian Peninsula have been reported as receiving suboptimal rehabilitation, often resulting in relapse and fatalities [56, 87, 88].…”
Section: Discussionmentioning
confidence: 99%
“…Given such background, traditional healing practices and illegal use of prescriptive medicines are rife and remain as the only recourse for people with substance use disorders in Arab countries [6, 85, 86]. Thus, people with substance use disorders in the Arabian Peninsula have been reported as receiving suboptimal rehabilitation, often resulting in relapse and fatalities [56, 87, 88].…”
Section: Discussionmentioning
confidence: 99%
“…Low research output in the field of substance-related disorders from Arab region might suggest lack of good mental health services and rehabilitation centres for substance abuse and addiction in the Arab countries [ 22 ]. A study carried out in Egypt found that patients with substance dependence had a significantly worse overall quality of life than the WHO standards [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the quality of life in the psychological domain one month after the intervention contributes to a difficulty presented in the national and international literature, which refers to losses in the quality of life of substance users (Marcon et al, 2012;Moreira et al, 2013 ;Muller, Skurtveit, & Clausen, 2016;Said, Okasha, Okasha, Haroon, & Fikry, 2012). Such domain is composed of the facets of self-esteem, body image and appearance, positive feelings and negative thoughts, learning processes, memory and concentration, spirituality, religion and personal beliefs (Fleck et al, 1999).…”
Section: Discussionmentioning
confidence: 99%